2014
DOI: 10.1016/j.fcl.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Scarf Osteotomy

Abstract: The term scarf osteotomy was first used by Weil when presenting his results from more than 1000 cases. Scarf is a carpentry term describing beveling the ends of 2 pieces of wood and securely fastening them so that they overlap to create one continuous piece. This technique was popularized by Weil and Barouk as a versatile method of correcting hallux valgus while maintaining the blood supply to the metatarsal head. It also has rigid fixation, allowing early mobilization. This article addresses the surgical tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
1
23
1
Order By: Relevance
“…Several authors reported in the past satisfactory results of the scarf osteotomy regarding pain relief, functional improvement, and deformity correction. [1][2][3]9,11,15,23,25 In the current study, deformity was corrected from mean preoperative HVA of 35.8 degrees and IMA of 14.1 degrees to postoperative HVA of 13.7 degrees and IMA of 6.9 degrees. Overall, the HVA was reduced in 22.2 degrees and IMA was reduced in 7.1 degrees.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several authors reported in the past satisfactory results of the scarf osteotomy regarding pain relief, functional improvement, and deformity correction. [1][2][3]9,11,15,23,25 In the current study, deformity was corrected from mean preoperative HVA of 35.8 degrees and IMA of 14.1 degrees to postoperative HVA of 13.7 degrees and IMA of 6.9 degrees. Overall, the HVA was reduced in 22.2 degrees and IMA was reduced in 7.1 degrees.…”
Section: Discussionmentioning
confidence: 67%
“…While a proximal chevron osteotomy is different from a scarf osteotomy, the operative principles of addressing the IMA and HVA components of HV deformity are similar. The study included 117 feet, with a mean follow-up of 14.2 months (range, [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Authors reported deformity correction with HVA reduction from 36.1 degrees (range, 16-44 degrees) to 5.4 degrees, and IMA reduction from 19 degrees (range, 9-28 degrees) to 4.5 degrees (range, -5 to 14.2 degrees).…”
Section: Discussionmentioning
confidence: 99%
“…Scarf osteotomy is suggested for the treatment of mild or moderate hallux valgus deformity and is defined as an osteotomy that translates the distal fragment laterally. 7 Scarf osteotomy has gone through several modifications in time. In one of these modifications, the distal plantar fragment was rotated laterally and a more efficient correction effect was targeted in the IMA without much impact on the DMAA.…”
Section: Introductionmentioning
confidence: 99%
“…Scarf is a carpentry term describing beveling the ends of 2 pieces of wood and securely fastening them so that they overlap to create one continuous piece. This technique was popularized by Weil and Barouk as a versatile method of correcting hallux valgus while maintaining the blood supply to the metatarsal head [16]. .…”
Section: Introductionmentioning
confidence: 99%